2010
DOI: 10.2319/012010-43.1
|View full text |Cite
|
Sign up to set email alerts
|

Bracket bond strength comparison between new unfilled experimental self-etching primer adhesive and conventional filled adhesives

Abstract: The unfilled experimental SEP adhesive system showed a clinically sufficient SBS that was equivalent to the filled SEP adhesive system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
2
12
1
1
Order By: Relevance
“…In the present study, a 4-META/MMA-TBB-based resin without BG was used as a control, and the mean bond strength thereof was 11.12 MPa. This value is very similar to the published value of 11.8 MPa for the same material (28). There were no significant differences in mean bond strength between the control specimen and BG-containing 4-META/MMA-TBB-based resins, with the exception of one specimen group with high BG content (50%).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, a 4-META/MMA-TBB-based resin without BG was used as a control, and the mean bond strength thereof was 11.12 MPa. This value is very similar to the published value of 11.8 MPa for the same material (28). There were no significant differences in mean bond strength between the control specimen and BG-containing 4-META/MMA-TBB-based resins, with the exception of one specimen group with high BG content (50%).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, Super-Bond/F3 released relatively a large amount of fluoride during the 6-month period, which was significantly greater than the value for Transbond Plus, but lower than the value for Fuji Ortho LC, except first day. Although Super-Bond/F3 requires self-etching for the bracket-bonding procedure 19) , the fluoride-releasing ability of Super-Bond/F3 may promote remineralization of the enamel around the bonded bracket on the enamel surface 13,20) . The use of cross-sectional microhardness measurements with a Knoop indenter has been a popular method for quantitatively investigating the demineralization of enamel 6,8,9) , since there is a strong correlation (R 2 =0.84-0.92) between enamel microhardness and mineral content determined by transversal microradiography in carious lesions 8,21,29) .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown that RMGIC are more effective for preventing the demineralization of enamel than both fluoride-releasing and non-fluoride-releasing composite resin adhesive systems 2,6,9) , although RMGIC were shown to have a lower bond strength than composite resin adhesives 4,5) . A recent study 11) investigated the shear bond strength of a new unfilled experimental self-etching primer (SEP) adhesive system that incorporates 4-META (4-methacryloxyethyl trimellitate anhydride)/MMA-TBB (Methyl methacrylate-tri-n-butyl borane)-based resin, and reported that this experimental adhesive system produced a milder etching pattern and an equivalent SBS. As another advantage, with the experimental SEP adhesive system, it may be easier to remove residual adhesive after debonding since it does not contain filler particles, which greatly influence the grindability of a composite resin adhesive 12) .…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain a smooth and glossy restoration surface, residual adhesives must be carefully removed and polished with finishing-polishing kits so that discoloration and plaque accumulation could be prevented. The failure site is highly influenced by the bond strength between the substrate and the adhesive resin, the strength of the bond between the adhesive resin and the bracket base, and the mechanical properties of the adhesive resin [30]. In the present study, the highest amount of residual adhesives left on the IRC after HF conditioning.…”
Section: Discussionmentioning
confidence: 69%